2007 IEEE International Conference on Industrial Engineering and Engineering Management 2007
DOI: 10.1109/ieem.2007.4419457
|View full text |Cite
|
Sign up to set email alerts
|

A Two-phase algorithm for the manufacturer’s pallet loading problem

Abstract: We propose a two-phase algorithm for solving the manufacturer's pallet loading problem (MPLP). A new integer linear programming model is developed to obtain the maximum number of items that could be packed onto a pallet in the first phase. The solution obtained in the first phase is then adopted to generate a layout pattern for the MPLP with a constraint programming model in the second phase. The computational results indicate that this algorithm can solve difficult instances to the optimality within reasonabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Some exact algorithms based on mathematical models require a sub-algorithm to determine the layout of an optimal solution (Beasley, 1985;Wu & Ting, 2007). To obtain the layout of a solution, they solved another mathematical model.…”
Section: Discussionmentioning
confidence: 99%
“…Some exact algorithms based on mathematical models require a sub-algorithm to determine the layout of an optimal solution (Beasley, 1985;Wu & Ting, 2007). To obtain the layout of a solution, they solved another mathematical model.…”
Section: Discussionmentioning
confidence: 99%
“…Alvarez-Valdes, Parreño, and Tamarit (2005b) proposed a branch and cut algorithm using Beasley's (1985) formulation and found the optimal solutions for the problems introduced by Alvarez-Valdes, Parreño, and Tamarit (2005a); however, the required computing time was quite long. Wu and Ting (2007) developed a two-phase algorithm based on a new integer programming model. In the first phase, they obtained the maximum number of boxes that could be loaded onto a pallet.…”
Section: Existing Researchmentioning
confidence: 99%
“…On the other hand, existing software like CPLEX, LINDO and CPN Tools has also been employed in the research of a solution for the PLP in [1], [4], [5] and [37]. Table 1 was developed to summarize the technique used in each of the approaches reviewed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It could be observed that the majority of them use exact algorithms with the incorporation of heuristics. The conformation of blocks (G4, G5), patterns or groups the heuristic method more widely employed when solving the PLP in either of its two variations as in the works of [1], [6], [7], [10], [14], [17], [31], [34], [37], [38] and [39]. Heuristics are normally used within these solution methods because they allowed the possibility to reduce computational time for this NPhard problem.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation